Two Decades of Community-Based Marine Conservation Provide the Foundations for Future Action - Villaseñor-Derbez, Juan Carlos; Amador-Castro, Imelda G.; Hernández-Velasco, Arturo; Torre, Jorge; Fulton, Stuart (Frontiers in Marine Science, 2022)
As a member of the ”High Level Panel for a Sustainable Ocean Economy”, Mexico has committed to expand community-based marine conservation. We draw from more than two decades of experience to outline how existing resources may be leveraged to help inform the country's ambitious conservation plans: - A total of 514.95 km^2 have already been protected under community-based marine reserves. - 14 years of ecological survey data, more than 130 community surveyors, more than one hundred publications, and an entire digital infrastructure provide a solid platform on which to continue building the community-based marine conservation movement. - Parallel and complimentary efforts have advanced regulation, action, data access and transparency, and coordination. - Future interventions should innovate, but leverage existing resources and continue to involve communities.